Forns index and fatty liver index, but not FIB-4, are associated with indices of glycaemia, pre-diabetes and type 2 diabetes: analysis of The Maastricht Study - Annemarie Koster; Ger Koek; Geert Robaeys; Otto Bekers; Simone Eussen; Pieter Dagnelie; Bastiaan de Galan; Casper Schalkwijk; Marleen van Greevenbroek; Coen Stehouwer; Leen Heyens; Hanna Kenjic; et al. (BMJ Open Gastroenterology)
Objective Glucose metabolism status (GMS) is linked to non-alcoholic fatty liver disease (NAFLD). Higher levels of advanced glycation end products (AGEs) are observed in people with type 2 diabetes mellitus (T2DM) and NAFLD. We examined the association between GMS, non-invasive tests and AGEs, with liver steatosis and fibrosis.Methods Data from The Maastricht Study, a population-based cohort, were analysed. Participants with alcohol overconsumption or missing data were excluded. GMS was determined via an oral glucose tolerance test. AGEs, measured by skin autofluorescence (SAF), were assessed using an AGE Reader. Associations of GMS and SAF with the fibrosis-4 score (FIB-4), Forns index (FI) and fatty liver index (FLI) were investigated using multivariable linear regression, adjusted for sociodemographic, lifestyle and clinical variables.Results 1955 participants (56.6%) were analysed: 598 (30.6%) had T2DM, 264 (13.5%) had pre-diabetes and 1069 (54.7%) had normal glucose metabolism. Pre-diabetes was significantly associated with FLI (standardised regression coefficient (Stβ) 0.396, 95% CI 0.323 to 0.471) and FI (Stβ 0.145, 95% CI 0.059 to 0.232) but not FIB-4. T2DM was significantly associated with FLI (Stβ 0.623, 95% CI 0.552 to 0.694) and FI (Stβ 0.307, 95% CI 0.226 to 0.388) but not FIB-4. SAF was significantly associated with FLI (Stβ 0.083, 95% CI 0.036 to 0.129), FI (Stβ 0.106, 95% CI 0.069 to 0.143) and FIB-4 (Stβ 0.087, 95% CI 0.037 to 0.137).Conclusion The study showed that adverse GMS and higher glycaemia are positively associated with steatosis. FI, but not FIB-4, was related to adverse GMS concerning fibrosis. This study is the first to demonstrate that SAF is positively associated with steatosis and fibrosis.